Bacteriological Pollution of Ground Water in Textile City Bhilawara, Rajsthan (India) - Hussain, J.; Hussain, I.; Ojha, K.G.; Sharma, K.C. (Asian Journal of Chemistry, 2010)
The growing population and inadequacy of municipal water supply has led to exploitation of ground water resources for drinking water. However, the quality of ground water has deteriorated substantially due to malpractice in sewage and garbage disposal. Ths study was carried out to evaluate the quality of ground water in urban area of Bhilwara. The bacteriological analysis of 107 samples from various areas in the town revealed that in Gulmandi area and near Sanganer gate area, the water contains an exceeding high number of coliforms and, therefore, is not suitable for human consumption.